Key Lessons from Successful Management of Inadvertent Intra-lenticular Bevacizumab Injection - Praneetha Sekar; Arokiam John Bosco; R Kavitha Josephine; Mudaliar Ashwini Elango (TNOA Journal of Ophthalmic Science and Research)
Intravitreal injections are a common therapeutic intervention practiced worldwide. However, this procedure carries a risk of injury to the lens, potentially leading to the development of an iatrogenic cataract. This case report details a patient who sustained posterior capsular injury during intravitreal injection of bevacizumab, resulting in an iatrogenic cataract. This report discusses the management and restoration of vision, highlighting the role of anterior segment optical coherence tomography (AS-OCT) in assessing the injury and guiding surgical intervention. Since the primary injury involved posterior capsule, surgical approach was comparable to that used in managing a posterior polar cataract.